Maternal risk factors and perinatal outcome in meconium stained amniotic fluid: a cross sectional study - Mohan, Meera; A. V., Deepak (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Meconium staining of amniotic fluid has long been regarded as a sign of fetal distress and fetal asphyxia. Although exact cause is unknown, meconium is thought to be passed from fetal gastro-intestinal tract as a response to hypoxia, mesenteric vasoconstriction induced gut hyper peristalsis, vagal stimulation and normal physiologic function of a mature fetus. Overall frequency has ranged from 5 to 24.6%. Present study is undertaken to detect incidence, mode of delivery, fetal heart rate variability and neonatal outcome in neonates born through MSAF. The objective of the study was to maternal risk factors, mode of delivery and perinatal outcome in labors complicated with meconium stained amniotic fluid. Methods: This is a cross sectional study done at Government Medical College, Thrissur on term, singleton pregnancies complicated with meconium stained amniotic fluid satisfying the inclusion criteria. Patients detailed history, gestational age, per abdominal examination, per speculum and per vaginal examination, admission tests including intrapartum cardiotocography (CTG) was recorded in a predesigned proforma. Results: The age of the patients varied between above 19 and 30 years. Majority of the study population were 69.3% Primi gravidas. Out of 130 cases, 56.2% were grade 2 meconium stained liquor, 30.7% were grade 3 meconium stained and 13.1% were grade 1 meconium stained. Association between neonatal complications in relation to grades of meconium was found to be statistically significant (p = 0.001). NICU admission was 24.7% in grade 2 meconium group. Hypoxic Ischemic encephalopathy was high in grade 3 meconium group, 45%. Majority of babies born through grade 1 meconium were asymptomatic and 10% of babies in grade 3 meconium groups were asymptomatic. Meconium aspiration syndrome, Respiratory distress were more in babies born through deliveries complicated with grade 3 meconium. Conclusions: The study indicated meconium stained amniotic fluid during labour increases the prevalence of abnormal intrapartum CTG, Caesarean section, lower Apgar score, increased duration of NICU and hospital stay, poor perinatal outcome and non-significant difference in incidence of lower birth weight in babies.